Potential of Using Ethanol as Fuel in the Transportation Sector - Sittimont, Faosie; Chinda, Thanwadee (Science & Technology Asia, 2025)
Ethanol is considered a renewable energy source which could be blended with fossil fuels to reduce carbon dioxide emissions. Since the production of ethanol involves various processes, numerous studies have found that one of the processes significantly impacting climate change is the acquisition of raw materials. Therefore, this research will focus on calculating the carbon dioxide emissions that impact global warming from the processes of obtaining fresh and burnt sugarcane, which are the primary raw materials in the production of molasses and subsequently using molasses to produce ethanol. 1 ton of ethanol was used as a functional unit. This research was analyzed following Thailand Greenhouse Gas Management Organization (Public Organization) and the fifth Intergovernmental Panel on Climate Change report. The results illustrate that the acquisition of fresh cane has the greatest impact on carbon dioxide emissions per functional unit (kgCO2eq/FU), accounting for 31.20% of the total. Moreover, the acquisition of burnt sugarcane has a high value at 22.29%. However, if we compared to the same quantity proportion, the emissions factor from burnt sugarcane are higher than those from fresh sugarcane due to open burning. These values were calculated based on the use of nitrogen-containing fertilizers, which account for 56.73%. This is the highest proportion in the sugarcane production process. In Thailand, the demand for renewable energy continues to rise. Therefore, this research aims to enhance the necessary database for analyzing LCA related to ethanol, as well as to find ways to minimize potential impacts as much as possible.